RMTS: A Novel Approach to Transmission Scheduling in Ad Hoc Networks by Salvaging Unused Slot Transmission Assignments - Bollapragada Subrahmanya, Vikas; Russell, Harlan B. (Wireless Communications and Mobile Computing, 2018)
In mobile ad hoc networks (MANETs) there is no centralized supervision over the network operations. In such networks, it is imperative to have protocols that are implemented locally in a distributed manner. To achieve high network performance utilizing only the wireless channels a distributed transmission-scheduling medium-access control (MAC) protocol is desirable. This type of protocol can guarantee a certain level of quality of service (QOS) and works well in congested networks. However, the transmission schedules are often decided in advance and if a node does not have a packet to transmit in its assigned slot then the slot is unused. We propose a protocol called recovering minislots transmission scheduling (RMTS) that salvages these unused transmission slots that would have otherwise been wasted. We show that the proposed protocol produces significant improvements in network performance over traditional transmission-scheduling approaches.